Melvilovi postupci kao izazov: mimetičnost kao redundanca junaka? (Philologia, 2021)
The aim of the paper is to reconsider the aspects of characterization of Tommo, Melville’s first hero, in the novel Typee, a Peep at the Polynesian Life, published in 1846. After summarizing the basic aspects of characterization in general, we have concentrated on the situational demonstration of his peronality and hero’s psychology in certain phase of his life. We have concluded that the concept of characterization in the first novel is rather complex, and that nominalization and the portrayal of the hero, especially the way in which the corporeal is presented in the novel, are highly important, both for the sailors who leave the ship at Nuku-hiva, and for the islanders that they meet there. In the theoretical sense we have based our research upon the work of D. Vukicevic, M. Bakhtin, W. Dillingham, and P. Bellis.